Brand equity of team sports towards sponsorship in Indonesian football club - Lukman, Syauqy; Nasution, Reza Ashari (Jurnal Manajemen Teknologi, 2010)
This is a study concerning the result of sports sponsorship where the research focuses on how would a specific construct of Brand Equity would correlate with the sponsorship outcome. The study takes one of the forerunners of professional football (soccer) club as the object. Persib (Persatuan Sepakbola Indonesia Bandung), a football club which resides in Bandung. Persib has proven to be one of the most prominent football clubs in terms of business, fans, and professionalism. Each home game are watched by a minimum number of 40,000 spectators, and the company itself, PT. PBB (Persib Bandung Bermartabat, Inc.) has managed to generate a yearly income of approx. 12 Billion Rupiahs, income which is considered as the largest from a professional football club in Indonesia.The study is aimed to discover how the construct of BETS (Brand Equity of Team Sports) would influence the Sponsorship Outcome. Questionnaires were distributed to 403 fans of Persib Bandung, whom are ssociated with Viking community. The study modifies the concept of Bauer, et al. (2005) that applies the concept of Consumer Based Brand Equity from Keller (1993), and also the concept of Sponsorship Outcome (SO) from Gwinner and Swanson (2003). BETS is divided into four dimension; Awareness, Product-Related Attributes, Non Product-Related Attributes, and Brand Benefits. For the football context, each dimension is measured according to the characteristics of a football club. Product-related attributes consists of Athletic success, star player(s), coach, and management. Sponsorship Outcome is measured by; Sponsor recognition, attitude toward sponsor, sponsor patronage, and satisfaction with sponsor. The research would focus on observing SO on the context of general sponsorship of Persib, Honda, and PT. Daya Adira Mustika. The concepts are modified by researcher to fit research context. This study introduces a simpler construct to measure BETS from earlier model of Bauer, et al. And empirical test prove research hypothesis that BETS significantly affect SO using SEM, and dimensions of BETS correlates with SO. Simpler dimensions of BETS proposed by this study can accurately measure BETS, and the research also concluded Honda as the top of mind sponsor of Persib.Keywords: Sponsorship, Sports Marketing, Brand Equity, Structural Equation Modeling, Brand Equity ofÂ Team Sports, Sponsorship Outcome, Sport Sponsorship Marketing.